The case of the Development Bank of Southern Africa as a knowledge institution. - Mbada, Mduduzi Goodwill. (My University, 2014)
ABSTRACT This study interrogates the philosophy underpinning the establishment of knowledge institutions. In asking what knowledge institutions are, it endeavours to understand what role they play in producing, managing and transferring knowledge to targeted communities geared towards developing them and in growing sustainable economies. The study further singles out the Development Bank of Southern Africa (DBSA) as a case study since it took a decision to become a knowledge institution and also because this institution plays a pivotal role in financing economic development in South Africa and the Southern African region. To answer the research question, which is, what is a knowledge institution? The study appraises the DBSA against existing knowledge production, management and transfer practices presented in the literature reviewed. From that, it seeks to identify prospects for improvement in order for the DBSA to embrace knowledge as a strategic resource and by embracing knowledge as a strategic resource, the DBSA could play a valuable role in transforming the country’s economic situation. For the institution to achieve such a goal, the study recommends that the DBSA should review and strengthen its knowledge management strategy by focusing on improving its ICT portal, records and document management systems, skills training programmes and, most importantly, its internal and external communications to realise its potential for effective knowledge creation and transfer that is targeted at opportunity seekers. The study concludes by emphasising the importance of leveraging co-operation, partnerships and the support of board members and the National Treasury to ensure that the DBSA does indeed become a knowledge institution.
MM 2013
Keywords: Development Bank of Southern Africa, Knowledge management.